BCG Vaccine–associated Complications in a Large Cohort of Children With Combined Immunodeficiencies Affecting Cellular and Humoral Immunity. Issue 11 (7th September 2022) - Al-Herz, Waleed; Husain, Entesar H.; Adeli, Mehdi; Al Farsi, Tariq; Al-Hammadi, Suleiman; Al Kuwaiti, Amna Ali; Al-Nesf, Maryam; Al Sukaiti, Nashat; Al-Tamemi, Salem; Shendi, Hiba
Abstract : Aims: To present the details of Bacillus Calmette-Guérin (BCG)-vaccine associated complications (VACs) in combined immunodeficiencies (CID) patients. Methods: Five centers participated in this retrospective study and completed a data form, which included general patients' information, clinical and laboratory data. Results: Among 236 CID patients, 127 were BCG vaccinated. 41.9% of patients with family history of CID and 17.1% who were diagnosed by screening were BCG vaccinated. Twenty-three patients (18.1%) developed BCG-VACs. The median age of VACs was 6 months and the median time from vaccination to complications was 6 months. The highest rate of BCG-VACs was recorded in patients receiving the Russian BCG strain compared to the Tokyo and Danish strains. Univariate analysis of T-lymphocyte subsets showed increased odds of BCG complications in patients with CD3+, CD4+, and CD8+ counts of ≤250 cells/µL. Only CD8 + count ≤250 cells/µL had increased such odds on multivariate analysis. VACs were disseminated in 13 and localized in 10 patients. Localized complication occurred earlier after vaccination (median: 4 months) compared with disseminated ones (median: 7 months). There were no significant associations between sex, administered vaccine strain, serum immunoglobulins levels, lymphocyte subsets counts, and the chance of having either localized or disseminated BCG-related complications. Coclusions: Although contraindicated, many patients with CID continue to be vaccinated with BCG. Low CD8 + count is a risk factor for BCG–related complications and localized complications occurred earlier than disseminated ones. Considerations should be undertaken by health care authorities especially in countries with high incidence of CID to implement newborn screening, delay the time of BCG vaccine administration beyond 6 months of age and to use the relatively safer strains like the Danish and Tokyo ones.